Soleal and gastrocnemius vein thrombosis in a patient with a muscular hematoma. Issue 2 (2016) - Gonzálvez, Asunción María; Chacón, Paula; García-Sánchez, Florentino; Jiménez, David; Mellado, Meritxell; Monreal, Manuel
No abstract available